Preservação do Legado Industrial Através da Memória. Proposta de Salvaguarda da Fábrica Jerónimo Pereira Campos em Viana do Castelo - Jorge Silva Ribeiro (2020)
This dissertation intends, through memory, to reflect on the importance of the conservation and safeguarding of the industrial heritage. Investigating the specifics of designing on an industrial structure, looking for new uses for these spaces. To investigate the conversion process of these buildings, the Jerónimo Pereira Campos, Filhos Factory in Viana do Castelo served as a case study. Throughout the dissertation, a historical, descriptive and critical analysis of the national context was carried out. Highlighting the potential of these buildings and exploring new methods of intervention in the pre-existence and in its dynamization of the urban and social environment. The logic of the intervention goes through the rehabilitation of the existing building, keeping together all the structural fragments of greater relevance of the place. This proposal aims to adapt, perceive and propose a new modern that seeks to incorporate people.